Process optimization for deep eutectic solvent pretreatment and enzymatic hydrolysis of sugar cane bagasse for cellulosic ethanol fermentation. (November 2021) - Liu, Yao; Zheng, Xiaojie; Tao, Shunhui; Hu, Lei; Zhang, Xiaodong; Lin, Xiaoqing
Abstract: This study investigated cellulosic ethanol production from sugar cane bagasse (SCB) pretreated by triethylbenzyl ammonium chloride/lactic acid (TEBAC/LA) deep eutectic solvent (DES). The results showed that the pretreatment of SCB with TEBAC/LA DES at 120 °C for 4 h with 1:15 (solid to liquid ratio) resulted in the best cellulose digestibility (88.23 ± 1.24%), which was approximately 228% higher than that of untreated SCB. Furthermore, the maximum cellulosic ethanol concentration of 16.84 g/L was achieved using glucose (36.06 g/L) and xylose (7.36 g/L). Moreover, the ethanol productivity and yield were 0.70 g/(L·h) and 0.42 g/g fermentable sugar, respectively. The efficient bioconversion was ascribed to the remarkable delignification (88.72 ± 1.63%), xylan removal (73.93 ± 0.17%), along with optimum cellulose recovery (95.89 ± 1.54%). Importantly, the enzymatic hydrolysis digestibility remained unchanged after 5 times DES recycling process. Overall, it also provided an insight into the efficient SCB biorefinery of DES systems. Graphical abstract: Image 1